2019
DOI: 10.3390/su11061567
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Environmental Education on Tourists’ Future Visit Intentions to Leisure Farms in Mountain Regions

Abstract: The research problem of this study is to understand whether people with higher level of EE are more likely to choose farm stays for their vacation. The main aim of this study is to investigate the causal relationship between an individual's environmental education (EE) and their theory of planned behavior (TPB) decision-making process that leads to future visit intention. A convenient sampling method was used to survey visitors of Toucheng Leisure Farm in the mountain region of Taiwan; and a total of 600 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…This finding does not confirm previous studies [13,76], which found that customers' lack of awareness related to environmental practices makes it necessary to invest more in environmental education, thus showing how the environment can be helped through independent gestures. Recent research indicated that devoting in environmental education can be beneficial for agritourism businesses by effectively increasing the pool of their potential customers, who are more willing to revisit and purchase at a premium price [120]. Therefore, a major shift in thinking is required for ATBHs owner-managers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding does not confirm previous studies [13,76], which found that customers' lack of awareness related to environmental practices makes it necessary to invest more in environmental education, thus showing how the environment can be helped through independent gestures. Recent research indicated that devoting in environmental education can be beneficial for agritourism businesses by effectively increasing the pool of their potential customers, who are more willing to revisit and purchase at a premium price [120]. Therefore, a major shift in thinking is required for ATBHs owner-managers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they should focus on raising tourists' awareness regarding the importance of saving water and energy within the rural destination they are visiting and within the unit they are accommodated in. Such accommodation units might collaborate with government agencies and nonprofit organizations that aim for environmental protection in order to promote environmental education among visitors [120]. Second, these units may implement various environmental education methods such as advertising the environmental commitment in their facilities and inviting guests to participate in environmentally-friendly activities, ecological corners with brochures or multimedia presentations, and seminars on environmental themes.…”
Section: Discussionmentioning
confidence: 99%
“…It includes rational predictors and assigns to self-interest motives and also to pro-social motives [42]. Numerous scholars pointed out the need to add pro-social variables to the TPB model, which has been successfully and broadly pragmatic in several studies to explicate various aspects of environmental behaviors, such as sustainable healthcare [43], green hotels [44,45], tourism studies [46], house rentals [47], rural development [48], the fashion industry [49], picking up litter in protected areas [50], urban bike-sharing for holiday cycling [51], sustainable agriculture [52][53][54], sustainable education [55], sustainable heritage tourism [56], sustainable consumption [57], energy-saving [58], water conservation [59,60], e-waste recycling [61], and sustainable transportation [62]. Henceforth, the extended TPB model was revealed to have stronger predictive power than the original TPB model [63].…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Mohiuddin et al (2018) [95] determined the impacts of environmental awareness on students’ willingness to buy green vehicles with a TPB framework. Leelapattana et al (2019) [96] used environmental education as an antecedent variable of the TPB to reveal the impact of environmental education on consumers’ intention when choosing a farm vacation. In addition, other extension factors are often used in related studies, such as environmental performance [97,98,99], self-identity [76,100], government incentives [64,92], and environmental values [101,102].…”
Section: Bibliometric Analysismentioning
confidence: 99%